Chronic obstructive pulmonary Disease and risk of mortality in patients with venous thromboembolism - the Tromsø Study - Børvik, Trond; Brækkan, Sigrid Kufaas; Evensen, Line; Brodin, Ellen Elisabeth; Morelli, Vania Maris; Melbye, Hasse; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2019)
Background - Previous studies have shown increased mortality in venous thromboembolism (VTE) patients with chronic obstructive pulmonary disease (COPD), but it is unknown to what extent the association is influenced by the severity of COPD and physical inactivity. Objectives - This article investigates whether COPD, and stages of COPD, influenced the risk of mortality after a first episode of VTE when physical inactivity was taken into account. Methods - Patients with a first lifetime VTE ( n = 256) were recruited among individuals who participated and performed spirometry in the fifth (2001–2002) and sixth (2007–2008) surveys of the Tromsø Study ( n = 9577). All-cause mortality was registered up to December 31, 2015. Results - There were 123 deaths during a median of 2.9 years of follow-up. The overall mortality rate was 11.9 (95% confidence interval [CI] 10.0–14.2) per 100 person-years. The risk of death was twofold higher in COPD patients compared with those with normal airflow (hazard ratio [HR] 2.00, 95% CI 1.30–3.08) after multivariable adjustment. The risk of death increased with the severity of COPD. VTE patients with COPD stage III/IV had a fivefold increased risk of death (HR 5.20, 95% CI 2.65–10.2) compared with those without COPD, and 50% of these patients died within 3.5 months after the incident VTE event. Adjustment for physical inactivity had minor effect on the risk estimates. Conclusion - VTE patients with COPD had increased risk of death, particularly patients with severe COPD. The detrimental effect of COPD on mortality in VTE patients was apparently explained by factors other than physical inactivity among patients with COPD.